LEARNING TO WRITE POETRY BY USING AN ACROSTIC TECHNIQUE ON CLASS X STUDENTS IN SMK - Maryam Jamilah; Teti Sobari (IKIP Siliwangi, 2019)
Learning to write poetry by using an acrostic technique on the class X students in SMK. The background problem in this research is that most students are not interested in writing poetry because poetry is considered as difficult; they have difficulty finding imagination and figurative words. The researchers have three research objectives based on this problem. Namely to describe the teachers and students activities when learning to write poetry by using an acrostic technique, to describe students' responses on learning to write poetry using an acrostic technique, to discover the difference between the results of the initial test and the final test in class X students at SMK. In this research, the Pre-Experimental Designs (non-design) method of one group pretest-posttest design is used and a research towards a class with 28 students is conducted. Observations, tests, and questionnaires are used as the research techniques. The results of the data obtained are the increase in student value. The average value before using the acrostic technique is 40.35 and the average value after using the acrostic technique in learning to write poetry is 79.00, the significance value indicates 0,000 based on the t test. The value is smaller than 0.05, thus the data is different from the results of the initial test and the final test. In other words, H0 is rejected and Ha is accepted. Thus, it can be concluded that learning to write poetry using an acrostic technique increases students' ability to write poetry.